The Influence of Seed Sowing Times and Rate of Fertilizer Application on the Total and Productive Number of Stemps - Kushmatov Bakhtiyor Sa'dullayevich (American Journal of Biodiversity, 2024)
In this article, the interaction of seeding rate, planting time and mineral fertilizer feeding rates on total stemps, productive stemps and productive stand of triticale in conditions of dry typical gray soils of Jizzakh region is studied and scientifically substantiated.